2005
DOI: 10.1097/00131746-200509000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo-Controlled, Exploratory Trial of Chromium Picolinate in Atypical Depression: Effect on Carbohydrate Craving

Abstract: : In a population of adults with atypical depression, most of whom were overweight or obese, CrPic produced improvement on the following HAM-D-29 items: appetite increase, increased eating, carbohydrate craving, and diurnal variation of feelings. In a subpopulation of patients with high carbohydrate craving, overall HAM-D-29 scores improved significantly in patients treated with CrPic compared with placebo. The results of this study suggest that the main effect of chromium was on carbohydrate craving and appet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 73 publications
0
26
1
2
Order By: Relevance
“…Although chromium picolinate was used with the purpose to induce fat loss and decrease carbohydrate craving, previous studies found no benefits of chromium picolinate supplementation in inducing fat loss 108,122,123 and appetite control. 123 However, a previous study suggested that chromium picolinate was beneficial in a subpopulation of patients with high carbohydrate craving, suggesting it may be beneficial for patients with atypical depression who also have severe carbohydrate craving, 124 which may be the case in some bodybuilders. It is important to note that the safe dose of chromium was not established and the amount used by the participants was significantly above the recommended upper limit, which could have a negative health impact.…”
Section: Discussionmentioning
confidence: 99%
“…Although chromium picolinate was used with the purpose to induce fat loss and decrease carbohydrate craving, previous studies found no benefits of chromium picolinate supplementation in inducing fat loss 108,122,123 and appetite control. 123 However, a previous study suggested that chromium picolinate was beneficial in a subpopulation of patients with high carbohydrate craving, suggesting it may be beneficial for patients with atypical depression who also have severe carbohydrate craving, 124 which may be the case in some bodybuilders. It is important to note that the safe dose of chromium was not established and the amount used by the participants was significantly above the recommended upper limit, which could have a negative health impact.…”
Section: Discussionmentioning
confidence: 99%
“…However, insulin receptors are ubiquitously found in the central nervous system and insulin affects distinct cognitive processes [58]. Chromium supplementation downregulates brain serotonin receptor and increases brain tryptophane, serotonin, noradrenaline, and pineal melatonin, which are linked to insulin sensitivity and depression [59][60][61][62]. In experiments involving animals, however, it is impossible to examine directly the level of depression, but some behavioral features can be attributed to central nervous system activity.…”
Section: Discussionmentioning
confidence: 99%
“…The chromium doses were chosen in light of prior studies in non-BED populations. This literature strongly suggested that low doses of chromium (< 400 mcg/day) could be sufficient for upregulating insulin binding and improving fasting glucose [42], moderate doses (600 mcg/day) could be sufficient to reduce depressive symptoms and cravings [23, 24], but 1000 mcg/day would be necessary to prevent weight gain [21, 43]. Because 1) avoidance of weight gain is such a critical factor in compliance and retention in overweight individuals seeking BED treatment, and 2) there is a theoretical concern of prolonged high dose exposure, establishing the minimum effective dose of chromium for binge abstinence and stabilization of metabolic parameters is an important long-term objective of our research.…”
Section: Methodsmentioning
confidence: 99%